Biological Significance of YAP/TAZ in Pancreatic Ductal Adenocarcinoma - Hayashi, Hiromitsu; Uemura, Norio; Zhao, Liu; Matsumura, Kazuki; Sato, Hiroki; Shiraishi, Yuta; Baba, Hideo (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) remains one of the most lethal types of cancer. Despite major advances in defining the molecular mutations driving PDAC, this disease remains universally lethal with an overall 5-year survival rate of only about 7–8%. Genetic alterations in PDAC are exemplified by four critical genes (KRAS, TP53, CDKN2A, and SMAD4) that are frequently mutated. Among these, KRAS mutation ranges from 88% to 100% in several studies. Hippo signaling is an evolutionarily conserved network that plays a key role in normal organ development and tissue regeneration. Its core consists of the serine/threonine kinases mammalian sterile 20-like kinase 1 and 2 (MST1/2) and large tumor suppressor 1 and 2. Interestingly, pancreas-specific MST1/2 double knockout mice have been reported to display a decreased pancreas mass. Many of the genes involved in the Hippo signaling pathway are recognized as tumor suppressors, while the Hippo transducers Yes-associated protein (YAP) and transcriptional co-activator with PDZ-binding motif (TAZ) are identified as oncogenes. By dephosphorylation, YAP and TAZ accumulate in the nucleus and interact with transcription factors such as TEA domain transcriptional factor-1, 2, 3, and 4. Dysregulation of Hippo signaling and activation of YAP/TAZ have been recognized in a variety of human solid cancers, including PDAC. Recent studies have elucidated that YAP/TAZ play a crucial role in the induction of acinar-to-ductal metaplasia, an initial step in the progression to PDAC, in genetically engineered mouse models. YAP and TAZ also play a key role in the development of PDAC by both KRAS-dependent and KRAS-independent bypass mechanisms. YAP/TAZ have become extensively studied in PDAC and their biological importance during the development and progression of PDAC has been uncovered. In this review, we summarize the biological significance of a dysregulated Hippo signaling pathway or activated YAP/TAZ in PDACs, and propose a role for YAP/TAZ as a therapeutic target.